A case of encephalopathy following a 10k run. Issue 6 (27th May 2022) - Carstairs, Claire; Jaffer, Fatima; Brex, Peter
Abstract : We present the case of a 47-year-old man who was admitted with unexplained delirium. He had taken part in a 10km running race three days before. He was admitted to intensive care one year earlier having presented with vomiting, seizures and encephalopathy. This occurred after a road trip in the USA with frequent steakhouse visits. No definitive diagnosis was made. His sister died at 57 from a presumed encephalitis after chemotherapy for breast cancer, but the diagnosis was uncertain. On initial examina- tion the patient was delirious but neurological examination was unremarkable. Blood tests revealed a low-grade neutrophilia with a normal CRP; ammonia was high (340 micromols/L); CK was normal; plasma amino acid profile showed a high glutamine level (1237micromol/L). EEG findings were in keeping with moderate encephalopathy. Genetic testing revealed hemizygosity for the X-linked pathogenic c. 118>T p.(Arg40Cys) mutation, indicating ornithine transcarbamylase (OTC deficiency). The patient's clinical state improved with supportive measures. He was referred to a specialist metabolic disorder clinic and has remained well. OTC deficiency is a rare but important cause of hyperammonaemic encephalopathy, which can be fatal. Targeted family history in cases of encephalopathy may be helpful. Diagnosis allows genetic counselling and successful management with straightforward methods including diet and exercise modification, dietary supplementation and "SOS" formulas for times of acute illness. We explore investiga- tion and management for under-recognised, important, causes of hyperammonaemic encephalopathy. claire.carstairs@nhs.net